Aerobic and anaerobic performances in tethered swimming - Papoti, M.; da Silva, A. S. R.; Araujo, G. G.; Santiago, V.; Martins, L. E. B.; Cunha, S. A.; Gobatto, C. A. (International Journal of Sports Medicine, 2013)
The purpose of this study was to investigate whether the critical force (CritF) and anaerobic impulse capacity (AIC) - estimated by tethered swimming - reflect the aerobic and anaerobic performance of swimmers. 12 swimmers performed incremental test in tethered swimming to determine lactate anaerobic threshold (AnTLAC), maximal oxygen uptake (VO2MAX) and force associated with the VO2MAX (i VO2MAX). The swimmers performed 4 exhaustive (tlim) exercise bouts (100, 110, 120 and 130% i VO2MAX) to compute the CritF and AIC (F vs. 1/tlim model); a 30-s all-out tethered swimming bout to determine their anaerobic fitness (ANF); 100, 200, and 400-m time-trials to determine the swimming performance. CritF (57.09±11.77 N) did not differ from AnTLAC (53.96±11.52 N, (P>0.05) but was significantly lower than i VO2MAX (71.02±8.36 N). In addition, CritF presented significant correlation with AnTLAC (r=0.76; P<0.05) and i VO2MAX (r=0.74; P<0.05). On the other hand, AIC (286.19±54.91 N.s) and ANF (116.10±13.66 N) were significantly correlated (r=0.81, p<0.05). In addition, CritF and AIC presented significant correlations with all time-trials. In summary, this study demonstrates that CritF and AIC can be used to evaluate AnTLAC and ANF and to predict 100, 200, and 400-m free swimming.